Advance signaling cost for multicast fast reroute proxy mobility management - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Abdullah, Azween; Mohd. Ramli, Huda Adibah; Islam, Shayla (Informatics (India) Ltd., 2016)
Mobile data traffic over IP has grown very rapidly in size. This huge increase in size creates high demand performance on network that supports mobile multicast services. This motivates the development of a better performance procedure with better signaling cost. Methods/Statistical analysis: A mathematical evaluation of signaling cost for multicast network mobility management namely Proxy Mobile IPv6 (PMIPv6). The signaling cost is derived from a novel combination of Multicast only Fast Reroute (MFR) and predictive Context Transfer (CT) with network mobility management. The signaling cost is designated base on the improved signaling call flow of the advanced method combination. It is calculated as the location updates and the packet delivery cost of the call flow. Findings: This combined procedure helps to mitigate unnecessary multicast network mobility traffic as usage increases. From the results it is clearly shows that the location update for the advanced signaling cost remain consistent regardless of the traffic usage. Where else for the standard method the signaling cost increases significantly, in parallel with the traffic increase. This is hardly because of the reduced location updates and the packet delivery cost of the novel combination procedure. Therefore through this implementation better signaling cost formula is brought forward. Application/Improvements: The advanced signaling cost helps to overcome performance degradation in multicast mobility management application such as live Internet video, Internet-video-to-TV, online video, webcam viewing, video conference and web-based video monitoring.